Black history-- white history : Britain's historical programme between Windrush and Wilberforce - Korte, Barbara; Pirker, Eva Ulrike (Historische Lebenswelten in populären Wissenskulturen, 2011)
"Britain's recent historical culture is marked by a shift. As a consequence of new political directives, black history began to be mainstreamed into the realm of national history from the late 1990s onwards. Black History-White History assesses a number of manifestations of this new cultural historiography on screen and on stage, in museums, and other accessible sites, emerging in the context of two commemorative events: the Windrush anniversary and the 1807 abolition bicentenary. It inquires about the terms on which the new historical programme could take hold, its sustainability, and its representational politics."--Publisher's website